Effective economic interests of agricultural integration in post-Soviet states (Journal of Economic Research & Business Administration, 2015)
Integration of the states is an interoperability and association of national facilities and creation of regional economic groups. Occurrence of the states in local or world economic system provides the way to creation of large commodity markets processing and manufacturing industries and in a plenty to let out the processed goods with the added cost. And together that, it helps introduction new innovative to technology and technics and thus will make structural variations to the external economic commerce. The agriculture is considered one of the most perspective branches in economy, which, possibilities having more and playing important value in social area and in constant manufacture. Nevertheless, the state economic reforms, the accepted regulatory and legal acts, still not in force to render special influence on progress of competitiveness of agriculture. In this connection, it should be noted that, it is necessary to develop new and effective mechanisms for increase of competitiveness of an agriculture.
Keywords: Agriculture; the CIS countries; agroindustrial integration; a security of food stuffs; economic efficiency; agroindustrial combines